Application of ‘KISS’ Principle on Marketing Mix Strategy (Firmax3 Product through Network Marketing in Indonesia): Case Study - Viendyasari, M (KnE Social Sciences, 2018)
The KISS Principle was first applied by the US Navy Organization in 1960. Now a days, the principle is also applied in various business organizations. The KISS (Keep It Simple Stupid) principle states that most systems work best if they are kept simple rather than made complicated; therefore, simplicity should be a key goal in design, and unnecessary complexity should be avoided. This study used descriptive qualitative methods, and the type of data in this study is divided into two parts: (1) Primary data that is obtained from the respondents through questionnaires, focus groups and panels, or data from interviews with researchers. (2) Secondary data is RF3 World, where it supports the research in the form of financial statement, profile and history of the company, and the structure of the organization. RF3 World applied KISS Principle and showed initial success through Network Marketing of FIRMAX3. The KISS Principle is applied to Marketing Mix Strategy, that is, Simple and Unique Product, Place Simple to Find Through Duplication, Simple and Low Promotion Cost Through Testimonial, Simple Price Strategy and Stupid People, all the strategy adopted by company is a customer-centric strategy. Keywords: Kiss Principle, marketing mix, network marketing, customer-centric strategy